The top-down strategies in an EFL class of the vocational high school: an experimental study on enhancing students listening comprehension skills - Badrun Larandang; Nur Sehang Thamrin; Andi Naniwarsih; Fikriani Aminun Omolu; Nadrun Nadrun (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Despite numerous studies emphasizing the benefits of using background knowledge and vocabulary in EFL listening courses, there is a lack of rationale for implementing top-down strategies that holistically integrate prior knowledge, vocabulary enhancement, and self-assessment. In order to address the issues, this study aimed to investigate the effectiveness of the teacher's top-down strategies in improving students' listening skills. Therefore, we utilized pre-experimental research, particularly a one-group pretest-posttest design, to ascertain the strategies effectiveness. Twenty-one participants in this study were selected randomly. We used paired sample T-test with SPSS software to figure out if there was a statistically significant difference between the pretest and post-test scores after repeated intervention encounters. The statistical analysis showed that the average post-test score (M= 77.8571) was considerably higher than the average pretest score (M= 63.5714). The findings indicated that the students listening proficiency improved after being addressed with top-down strategies. This finding suggests that the teachers top-down approach helps students raise their listening comprehension skills. The study's results call for using top-down strategies to stimulate students' listening comprehension, to learn more effectively, and increase their listening consciousness.